Gender-specific effects of cognitive functions in elite judokas - Korobeynikov, G.; Raab, M.; Korobeinikova, L.; Xin, H.; Pryimakov, O.; Barbas, I.; Bulatova, M.; Chernozub, A.; Goncharova, O.; Raximov, V.; Burnashev, R. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2025)
Problem. The aim of this study is to study cognitive properties and decision-making in judokas of different genders. This problem is relevant due to the great popularity of women`s judo and the need to restructure training in accordance with gender characteristics.